Long-term follow-up after colorectal endoscopic submucosal dissection in 182 cases - Suchy, Christian; Berger, Moritz; Steinbrück, Ingo; Oyama, Tsuneo; Yahagi, Naohisa; Dumoulin, Franz Ludwig (Endoscopy International Open, 2021)
Background and study aims We previously reported a case series of our first 182 colorectal endoscopic submucosal dissections (ESDs). In the initial series, 155 ESDs had been technically feasible, with 137 en bloc resections and 97 en bloc resections with free margins (R0). Here, we present long-term follow-up data, with particular emphasis on cases where either en bloc resection was not achieved or en bloc resection resulted in positive margins (R1).Patients and methods Between September 2012 and October 2015, we performed 182 consecutive ESD procedures in 178 patients (median size 41.0 ± 17.4 mm; localization rectum vs. proximal rectum 63 vs. 119). Data on follow-up were obtained from our endoscopy database and from referring physicians. Results Of the initial cohort, 11 patients underwent surgery; follow-up data were available for 141 of the remaining 171 cases (82,5 %) with a median follow-up of 2.43 years (range 0.15–6.53). Recurrent adenoma was observed in 8 patients (n = 2 after margin positive en bloc ESD; n = 6 after fragmented resection). Recurrence rates were lower after en bloc resection, irrespective of involved margins (1.8 vs. 18,2 %; P < 0.01). All recurrences were low-grade adenomas and could be managed endoscopically. Conclusions The rate of recurrence is low after en bloc ESD, in particular if a one-piece resection can be achieved. Recurrence after fragmented resection is comparable to published data on piecemeal mucosal resection.